Clinical and Inflammatory Benefits of Nebulized Furosemide with Salbutamol–ipratropium in COPD Exacerbations: A Randomized Controlled Trial - Mahdi Behi; Babak Gholamine; Mohammad Reza Masjedi; Alireza Eslaminejad; Esmaeil Idani; Mohsen Sadeghi; Akram Qanavati; Sayed Mehran Marashian; Esmaeil Mortaz; Atefeh Abedini; Mihan Pourabdollah; Bita Pakshad; et al. (Iranian Journal of Allergy, Asthma and Immunology, 2026)
Exacerbations of chronic obstructive pulmonary disease (COPD) are a leading cause of morbidity, mortality, and healthcare burden. While standard bronchodilator therapy alleviates airway obstruction, its efficacy is often limited. This study evaluated nebulized furosemide, which has bronchodilatory and anti-inflammatory effects, as an adjunct to salbutamol–ipratropium in hospitalized COPD patients. Ninety‑two patients with exacerbated COPD were randomly assigned to two equal groups (46 each). The intervention group received nebulized salbutamol–ipratropium plus furosemide (20 mg), and the control group received salbutamol–ipratropium, both every 8 hours for 10 minutes over 5 consecutive days. Demographic and clinical variables, pulmonary function indices (FEV1, FVC, FEV1/FVC), clinical outcomes (COPD Assessment Test (CAT), Modified Medical Research Council (mMRC)scores, and quality of life by St. George’s Respiratory Questionnaire (SGRQ)), arterial blood gases, and inflammatory biomarkers (TNF-α, IL-6, IL-8, CRP, ESR, neutrophil %, WBC) were measured before and after treatment. Demographic characteristics and baseline indices did not differ significantly between the groups. Dyspnea and respiratory symptoms (mMRC and CAT scores) decreased significantly, while quality of life, improved markedly in the intervention group compared to the control group. Pulmonary function also showed significant enhancement, with the FEV₁/FVC ratio increasing. Arterial blood gas analysis showed higher PaO₂ and lower PaCO₂ in the intervention group. IL-6 and IL-8 decreased significantly, and no adverse events were reported. Nebulized furosemide enhances standard therapy in COPD exacerbations, improving lung function, relieving symptoms, and reducing systemic inflammation. Its safety, accessibility, and low cost make it a promising adjunct treatment.